Building Reputation Through Environmental Disclosure - R.Rosiyana Dewi (Indonesian Management and Accounting Research, 2019)
Stakeholder’s concern for environmental sustainability makes corporate environmental responsibility become one of the company's requirements to improve reputation.  A well-managed environmental program will give some benefit for the surrounding community and also enhance the company's reputation. The purpose of this study is to explain the effect of environmental disclosure on corporate reputation and to explain whether the independent commissioner can moderate that influence. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) which received an assessment on Corporate Image Index, so the observations of this research is 80 samples. Method used for data analysis is using multiple regression test. This study uses the Corporate Image Index (CII) by Frontier Consulting Group as a measurement of the company's reputation as its novelty. The paper finds that environmental disclosure affects the company's reputation in Indonesia especially in manufacturing companies. In addition, this research proves that independent commissaries can moderate the influence of environmental disclosure against reputation. The research implications for managers are about the company's reputation can be improved through their responsibility to the environment described in the environmental disclosure.